THE CORRELATION BETWEEN VERB MASTERY AND STUDENTS’ ABILITY IN CONSTRUCTING COMPOUND SENTENCE OF 2017/2018 TENTH YEAR STUDENTS OF SMK SWASTA SATRIA BINJAI - Miswan Sujaka (UIN Sumatera Utara, 2018)
This research was aimed to find out the correlation between the students’ verb mastery and their ability in constructing compound sentence of tenth grade students of SMK Swasta Satria Binjai. Two kinds of tests were administered. The method of this research was the correlational research. The population of this study was the tenth grade students of SMK Negeri 1 Stabat in academic year 2017/2018. The number of the sample was 30 students. The data obtained by administering test to the Network Computerized Technical – 2 as sample. Data were analyzed using r-Product Moment. The result of r was 0.793. The value in 5% was 0.355 and in 1% was 0.456. So, the result showed that there was a significant correlation between the students’ verb mastery and their ability in constructing compound sentence of tenth grade students of SMK Swasta Satria Binjai. Based on the result of the research, it was important both for the English teachers and the students to realize one of the factors that gave positive contribution to the students’ ability in constructing compound sentence was their verb mastery.Keywords: verb, compound sentence, mastery.